2013
DOI: 10.4028/www.scientific.net/jnanor.26.111
|View full text |Cite
|
Sign up to set email alerts
|

Novel Enhanced Oil Recovery Method Using Co<sup>2+</sup><sub>x</sub>Fe<sup>2+</sup><sub>1-x</sub>Fe<sup>3+</sup><sub>2</sub>O<sub>4</sub> as Magnetic Nanoparticles Activated by Electromagnetic Waves

Abstract: Research on the application of nanoparticles, specifically magnetic nanoparticles in enhanced oil recovery has been increasing in recent years due to their potential to increase the oil production despite having to interact with reservoirs of high salinity, high pressure and temperature and un-natural pH. Unlike other conventional EOR agents e.g. surfactants and polymers, a harsh environment will cause degradation and failure to operate. Magnetic nanoparticles which are activated by a magnetic field are antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…In a simulation study [10], high magnetic susceptibility nanoparticles were recommended as the magnetic perturbation caused by nanoparticles within the pore wall will facilitate oil blob detachment, thus improving the oil recovery rate. As in Soleimani et al [11], higher magnetic susceptibility nanoparticles show better oil recovery rate in a core flooding test under EM wave irradiance.…”
Section: Introductionsupporting
confidence: 55%
“…In a simulation study [10], high magnetic susceptibility nanoparticles were recommended as the magnetic perturbation caused by nanoparticles within the pore wall will facilitate oil blob detachment, thus improving the oil recovery rate. As in Soleimani et al [11], higher magnetic susceptibility nanoparticles show better oil recovery rate in a core flooding test under EM wave irradiance.…”
Section: Introductionsupporting
confidence: 55%
“…However, a variety of factors, including NPs size, concentration, electromagnetic radiation frequency, etc., influence oil recovery. 84 As specified by Ryoo et al 85 magnetic NPs adsorb at the oil−rock interface in the vicinity of fluctuating magnetic fields, which is advantageous for changing wettability. It is believed that higher oil recovery will occur because a wettability change of the reservoir rock is a crucial occurrence.…”
Section: Nanofluids Of Iron Oxide (Fe 2 O 3 /Fe 3 O 4 )mentioning
confidence: 96%
“…Soares et al (2014) simulation study, high magnetic susceptibility nanoparticles were recommended as the magnetic perturbation caused by nanoparticles within the pore wall will facilitate oil blob detachment, thus improving the oil recovery rate. As studied by Soleimani et al (2014), higher magnetic susceptibility nanoparticles shown better oil recovery rate in a core flooding test under EM wave irradiance.…”
Section: Introductionmentioning
confidence: 94%